The influence of muscle fatigue on walking: The role of aging and Parkinson's disease - Dos Santos, Paulo Cezar Rocha [UNESP]; Orcioli-Silva, Diego [UNESP]; Simieli, Lucas [UNESP]; Pereira, Vinicius I.A. [UNESP]; Barbieri, Fabio A. [UNESP] (Springer Nature, 2017)
Muscle fatigue causes motor adjustments in functional activities, including locomotion. Fatigue development is mediated by a range of individual factors such as the presence of pathologies, age, physical activity level, and type of activity performed. Specifically regarding gait control, muscle fatigue conditions have been associated with changes in stability and safety. To understand how muscle fatigue affects walking, mainly in complex environments, such as obstacle crossing or stepping down a curb, and whether the motor adjustments are age and Parkinson's disease (PD)-related, our group conducted a series of experiments involving walking tasks and muscle fatigue. In these studies, we investigated the influence of physical activity level, age, PD, and complexity of the environment in the context of muscle fatigue and walking. In this chapter, firstly, we define muscle fatigue. Then, we explain how the physiology of muscle fatigue can influence motor control. Furthermore, we consider fatigue in the context of aging and PD and indicate the effects of muscle fatigue on gait parameters. Finally, we discuss the main findings from our studies, comparing them with the literature and pointing out the practical applications.
Keywords: Aging; Gait; Motor control; Muscle fatigue; Obstacle avoidance; Parkinson's disease; Physical activity level